ANALISIS IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH NOMOR 8 TAHUN 2016 TENTANG KAWASAN TANPA ROKOK (KTR) DI KABUPATEN INDRAMAYU TAHUN 2021 (STUDI KASUS TAHUN 2016-2021) - 19, Oktaviani Melky Seldjatem; Yulyanti, Depi; Widyastuti, Setyo Dwi (JURNAL KESEHATAN INDRA HUSADA, 2024)
The prevalence smoking in Indramayu Regerency 10 year old is 28.87% for daily smokers, 3.56% for occasional smokers. Purpose the study was to determine implementation of Regional Regulation No. 8 of 2016 about no smoking area in Indramayu District (Case Study 2016-2021). This study uses a qualitative method with a case study approach. There were 12 informants in this study, the main informants were the chairman of the DPRD, Head of Health Promotion Section of the Health Office, and Head of Community Development for Satpol PP, triangulation informants namely NGOs and 8 people in charge of KTR places. The results of the study stated that the dissemination of information had been conveyed to other agencies and executives, the socialization was not uniform and not consistent. The provision of special smoking room facilities is still not all provided, the allocation comes from the APBD and BOK, "no smoking" signs have been implemented which do not apply in public transportation and terminals. Ashtrays are provided in places of worship, workplaces and other places, cross-sectoral cooperation has been carried out, the application of KTR has not run optimally because there are still areas that do not have a Task Force and SOP. The conclusions in this study are seen from the factors of communication, resources, disposition and bureaucratic structure are still not optimal. Therefore, it is suggested to increase the factors that can influence the process of implementing public policy.